2011
DOI: 10.1016/j.cattod.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Application of atmospheric non thermal plasma-catalysis hybrid system for air pollution control: Toluene removal

Abstract: International audienceThe combination of heterogeneous catalysts with non-thermal plasma (DBD operated in sinusoidal mode) was investigated for the removal of toluene from air at room temperature. The DBD reactor gives the possibility to introduce the heterogeneous catalyst directly into the discharge zone (in-plasma catalysis, IPC) or to place the catalyst downstream the plasma zone (post-plasma catalysis, PPC). Various catalytic materials based on Ag, Au, Cu, Co, Mn, La, and Nb, supported on Al2O3 and CeO2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(44 citation statements)
references
References 29 publications
1
43
0
Order By: Relevance
“…According to the gas discharge theory, the load characteristics of a reactor are equivalent to that of a capacitor, and the DBD process can be equivalent to the charge and discharge transitions of the capacitor [2][3][4]10,24].…”
Section: Lissajous Figuresmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the gas discharge theory, the load characteristics of a reactor are equivalent to that of a capacitor, and the DBD process can be equivalent to the charge and discharge transitions of the capacitor [2][3][4]10,24].…”
Section: Lissajous Figuresmentioning
confidence: 99%
“…Dielectric barrier discharges (DBDs) have a number of industrial applications, such as surface modification, environmental protection, medicine, and plasma displays, because they can produce large volume and high-energy-density NTPs at atmospheric pressure over a wide range of frequencies without expensive vacuum equipment [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…However, by-products such as CO, CO 2 , and NO x seem unavoidable under operation of plasma reactors. In order to minimize the toxic products and improve the energy efficiency of the VOCs decomposition process by plasma, combination of heterogeneous catalysts has often been tested (Demidiouk et al 2003;Subrahmanyam et al 2006b;Harling et al 2007;Kim et al 2007a;Wallis et al 2007: Quoc An et al 2011. NTP in air produces ultra violet (UV) radiation due to excited nitrogen molecules; with a suitable combination of photocatalysts, performance of NTP may be further improved.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed the efficiency of non-thermal plasma catalysis (Guo et al 2006), condensation, membrane separation, biofiltration (Quoc An et al 2011;Zhao et al 2011), adsorption (Areerob et al 2015;Yakout & Daifullah 2014;Yang et al 2013), photocatalysis (Luo et al 2006;Momani & Jarrah 2009) and catalytic oxidation (Jothiramalingam & Wang 2007;Santos et al 2010) in the decomposition of VOCs present in the atmosphere. Though some processes are found to be effective, the ease of performing the process and the means of producing its precursors must also be taken into consideration.…”
Section: Introductionmentioning
confidence: 99%